Farmer field day training: Demonstrating the benefits of certified climate-smart potato varieties in Rwanda - Okonya, Joshua; Ilakut, Ben; Barungi, Julian; Odeke, Moses; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Field days are one of the proven approaches for exposing farmers to new and improved technologies and innovations, facilitating their adoption. Farmer field days not only increase knowledge among stakeholders, especially farmers, about good agricultural practices but also offer an opportunity for participants to see for themselves and interact with fellow participants. In February 2025, ASARECA and its partners established 11 on-farm, farmer-managed demonstration fields of two improved and climate-smart potato varieties (Cyerekezo and Ndamira) in the Shingiro sector of Musanze District, Rwanda. The objective was to facilitate access to clean potato seed of two potato varieties, specifically to over 300 members of Dukomeze Ubuzima Cooperative, the majority of whom are women and youth with disabilities. It is against this background that ASARECA, in partnership with the RAB and SPF-Ikigega, organized this farmer field day to complement ongoing initiatives aimed at increasing access to certified seed of improved, climate-smart potato varieties for the benefit of smallholder farmers, particularly youth and women. The field day and training: (i) sensitized smallholder farmers about existing climate smart potato varieties; (ii) evaluated the on-farm yield of certified climate smart potato varieties when managed by farmers; (iii) discussed the best post-harvest handling and storage of seed potato; (iv) identified barriers to adoption of improved varieties; and (v) highlighted the benefits of practicing good agronomic practices when using improved climate resilient potato varieties. The field day brought together 233 participants (83 males, 150 females). Participants comprised farmers, transporters, researchers, store owners, agro-input dealers, seed companies, media and staff of ASARECA Secretariat. The field day was funded under the auspices of ASARECA’s Comprehensive Africa Agriculture Development Program, Ex-Pillar 4 (CAADP-XP4), and the Accelerating Impacts of CGIAR Climate Research Africa (AICCRA) projects. The CAADP-XP4 project is funded by the European Union through the International Fund for Agricultural Development. The AICCRA project is supported by the World Bank through the Alliance of Bioversity and CIAT.